KINERJA PORTOFOLIO OPTIMAL PADA SAHAM BERBAGAI INDEKS DENGAN KALKULASI RASIO SORTINO, MODIGLIANI SQUARE, DAN ROY’S SAFETY FIRST - Baiq Nurul Suryawati; Laila Wardani; Sulaeman Sarmo; Iwan Kusmayadi (Distribusi - Journal of Management and Business, 2018)
The main purpose of this research is evaluating portfolio performance of variousindexes that comprises constituent index in Indonesia Stock Exchange. The performance of evaluation calculatesbasedon Sortino,Modigliani Square and Roy Safety First ratio. Hence, the difference between its portfolios performances will shows the significance of each market’s differentite. The indexesare LQ 45, Jakarta Islamic Index (JII), Indeks Saham Syariah Indonesia, and BISNIS 27. The result shows that there is significance different between the share markets whereas the investment pattern of portfolio will represents investor’s desired return. However, as the measurementrealize on adjusting return and risk, thus, it will necessary to enhance investor’s with more pragmatic method such as share price volatility to persuade more investment. Share price volatility, furthermore, will give more precise information about how return created to profit investors.